A Transdisciplinary Approach to Examining and Confidence-Boosting the Experiences of Chinese Teachers of Chinese in Finland - Haiqin Liu; Fred Dervin (L2 Journal, 2016)
With the current rise of China as a political, cultural, and economic superpower, Chinese as a foreign and second language has gained popularity worldwide. Finland is also responding to this global wave, as is reflected by the increasing number of Chinese courses in formal and informal settings in the Nordic country. Yet not all actors involved in the promotion of Chinese seem to experience instruction in the language in the same way. This study investigates how Chinese teachers of the Chinese language, who represent the majority of the ‘workforce’ for instruction in this language in Finland, perceive Chinese language education and their role in it.